Adverse events of rituximab in neuromyelitis optica spectrum disorder: a systematic review and meta-analysis. (December 2021) - Wang, Hao; Zhou, Juanping; Li, Yi; Wei, Lili; Xu, Xintong; Zhang, Jianping; Yang, Kehu; Wei, Shihui; Zhang, Wenfang
Background: The adverse events (AEs) of rituximab (RTX) for neuromyelitis optica spectrum disorder (NMOSD) are incompletely understood. Aim: To collate information on the reported the AEs of RTX in NMOSD and assess the quality of evidence. Methods: PubMed, EMBASE, Web of Science, Cochrane Library, Wanfang Data, CBM, CNKI, VIP, clinicaltrials.gov, and so on were searched for studies with control groups as well as for case series that had assessed the RTX-associated AEs. The incidence of AEs and the comparison of AE risks among different therapies were pooled. The GRADE was developed for evidence quality. Results: A total of 3566 records were identified. Finally, 36 studies (4 RCTs, 6 crochet studies, 2 NRCTs, and 24 case series), including 1542 patients (1299 females and 139 males), were included for final analyses. Rates of patients with any AEs, any serious AEs (SAEs), infusion-related AEs, any infection, respiratory infection, urinary infection, and death were 28.57%, 5.66%, 27.01%, 17.36%, 4.76%, 4.76%, and 0.17%, respectively. The results from subgroup analysis showed that AE rates were most likely not associated with covariates such as duration of illness and study designs. Very low-quality evidence suggested that the risk ratios (RR) of any AEs (0.84, 95% CI = 00.42–1.69, p = 0.62) and any infections (1.24 95% CI = 0.18–8.61) of RTX were similar to that of azathioprine, and the RR of any AEs of RXT was akin to that of mycophenolate mofetil (0.66, 95% CI = 0.32–1.35 p = 0.26). Evidence of low to high quality showed the lower RR of RTX in other AEs, but not in infusion-related AEs. Strategies to handle AEs focused on symptomatic treatments. Conclusions: RTX is mostly safer than other immunosuppressants in NMOSD: the incidence of RTX-associated AEs was not high, and when present, the AEs were usually mild or moderate and could be well controlled. Given its efficacy and safety, RTX could be recommended as a first-line treatment for NMOSD.